Kepemimpinan Profetik dalam Menumbuhkan Karakter Peserta Didik - Moh. Syamsul Falah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
The prophetic leadership model is a leadership model that is rarely studied. This leadership model is very suitable to be applied in various situations. Generally, the leadership model prioritizes scientific and experiential aspects only. Meanwhile, this prophetic leadership model requires a leader not only to have scientific and practical abilities, but also to have a strong faith or spirituality. This prophetic leadership is more attached to the uswah of the leader as the principal of the school, its ability which is driven from the aspects of high conscience and logic (intellectual intelligence) makes it easy for leaders to achieve success because what is dynamized is truth and intelligence. Such a leader's attitude makes motivation and inspiration for subordinates in shaping their character, including students in school. Based on the identification of the problems above, the researcher wants to answer the focus of the research question, namely how is prophetic leadership in fostering the character of students in school? The method of this research is conducted by library research as part of the qualitative research design. While data collection is carried out by researchers by collecting information that is relevant to the research context. This information can be obtained by researchers through books, scientific papers, and journals.